1998
DOI: 10.1046/j.1537-2995.1998.38298193095.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hyperoxic ventilation on hemodilution‐induced changes in anesthetized dogs

Abstract: In anesthetized dogs ventilated with room air and hemodiluted to a Hb of 7 g per dL, simple oxygen therapy by HV (FIO2 1.0) rapidly improves tissue oxygenation and permits extended hemodilution to Hb of 5.8 g per dL until the HV-induced effects are lost.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0
9

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(61 citation statements)
references
References 20 publications
0
52
0
9
Order By: Relevance
“…It has been observed, that hyperoxic vasoconstriction reverses hemodilution-induced vasodilation but does not lead to a significant increase in vascular resistance. 35,36 Not surprisingly, neither O 2 delivery nor regional blood flow nor peripheral tissue O 2 partial pressure have been found disturbed.…”
Section: Intestinal O 2 Transport Following Hyperoxic Ventilationmentioning
confidence: 94%
See 1 more Smart Citation
“…It has been observed, that hyperoxic vasoconstriction reverses hemodilution-induced vasodilation but does not lead to a significant increase in vascular resistance. 35,36 Not surprisingly, neither O 2 delivery nor regional blood flow nor peripheral tissue O 2 partial pressure have been found disturbed.…”
Section: Intestinal O 2 Transport Following Hyperoxic Ventilationmentioning
confidence: 94%
“…Similarly, other investigators observed a reduction of cardiac index, regional blood flow and Hb O 2 extraction following hyperoxic ventilation in extreme hemodilution. 8,10,37 Despite these potentially unfavorable effects, these authors report that hyperoxic ventilation was however followed by improved peripheral, 9,35,36 cerebral, 10 and myocardial oxygenation 9 as well as improved cerebral and myocardial function. 9,10 Since hyperoxic ventilation is capable to restore organ function in extreme anemia, 37 it is extremely unlikely that additional physically dissolved O 2 is merely shunted to the venous side of the circulation.…”
Section: Intestinal O 2 Transport Following Hyperoxic Ventilationmentioning
confidence: 98%
“…Endorganlardaki bu sellüler hipoksi ise miyokard hasarı, inotrop gereksiniminda artış, nörolojik bozulma ve inme, renal disfonksiyon ve postoperatif diyaliz, mekanik ventilasyon desteği süresinde uzama gibi sorunlarla sonuçlanmaktadır (25,27,35) . (36,37) . (38) .…”
Section: Anemi Ve Riskleriunclassified
“…It has been observed that haemoglobin solutions with different O 2 affinity caused different degrees of vasoconstrictions [61,62]. However, the hypothesis of autoregulatory vasoconstriction due to relative hyperoxic state caused by better O 2 unloading is in contradiction with multiples observation of better tissue PO 2 during hyperoxic ventilation [63][64][65][66][67][68].…”
Section: Modified Haemoglobin Solutionsmentioning
confidence: 99%
“…Animal models of haemodilution have shown the capacity of perflubron to restore peripheral tissue oxygenation with amelioration of organ function [63,133,134]. This is due most likely to favourable off-loading of O 2 in hypoxic tissue and to the small dimension of perflubron droplet as compared to erythrocytes allowing it to pass even very narrow or near totally obstructed vessels.…”
Section: Perflubron (Oxygent Tm )mentioning
confidence: 99%